CYBER ISLAMIC UNIVERSITY: Development of Digital Technology for Learning and Creative Economy at IAIN Syekh Nurjati Cirebon - Aan Jaelani (UIN Siber Syekh Nurjati Cirebon, 2022)
This article will explore the concept and application of the Cyber Islamic University (CIU), which is a priority program for institutional transformation in distance learning starting in 2021 as part of the transformation of institutes into universities and changes in financial governance from work unit-based financial management to service agency financial management (BLU) at IAIN Syekh Nurjati Cirebon. It is crucial to study the application of CIU as a new model of Higher Education of Islamic Religious (PTKI) which organizes distance education for students, academic development through the use of metaverse technology, and the development of digital entrepreneurship that presents a creative economy for the sustainability of educational services. This study uses a qualitative method by choosing a grounded theory approach to build the main concept of CIU and its application in universities. Data were obtained from unstructured interviews from various statements of informants who were actively involved in CIU's transformation and published on the media or website, then the data were analyzed by coding, concept formation, categorization, and theory formation stages. This research found that the institutional transformation of IAIN Syekh Nurjati Cirebon into Cyber Islamic University is a new model of higher education that organizes distance education for students to increase access to education that is inclusive for everyone. CIU for academic development through the use of metaverse technology to improve the quality of educational services that unite virtual worlds and reality that can be implemented for good values by presenting accessibility, diversity, equality, and humanity. Institutional transformation of the Public Service Agency's financial management can develop digital academic entrepreneurship with a creative economy platform that can increase income, create jobs, and simultaneously promote social inclusion, cultural diversity, and human development to strengthen educational services.